Eksistensi jam’iyyah perempuan pengasuh pesantren dan muballighah (JP3M) Pekalongan (Analisis postfeminisme Simone de Beauvoir) - M. Badruz Zaman; Nur Aeni (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Facts show to this day, women still become one of the men's dominant objects. The patriarchal culture that marginalizes women has finally become one of the significant human tasks, both in the domestic and public scopes. Through the author's reading of Simone de Beauvoir's theory of post-feminism, this article tries to provide a description of the results of the field research at Pesantren and Muballighah Women Community (JP3M) Pekalongan Branch. In short, Beauvoir gives women the freedom to survive with the power and domination of men or free themselves from the shackles of patriarchy. According to the author's simple research results, several findings were found that JP3M seeks to increase the role of women in various fields of life, such as education and religion (intellectual), economic independence through micro-enterprises and provision of life skills, social transformation of the society by carrying out social activities, and wanting to break away as others through empowering women who are strong and with character.